Effect of aqueous herbal extracts on growth, plasma metabolites and meat characteristics of broiler (Bangladesh Journal of Animal Science, 2020)
The experiment was carried out for 4 weeks to find out the efficacy of herbal extracts supplementation in drinking water on production performance, plasma metabolites, carcass characteristics, and fat deposition of commercial broilers. A total of 200 straight run day-old chicks (Cobb-500) were divided into five treatment groups; T0=Basal diet, T1= Basal diet+10 ppm neem leaves extract, T2= Basal diet+10 ppm garlic leaves extract, T3= Basal diet+10 ppm plantain leaves extract, T4= Basal diet+10 ppm antibiotic growth promoter (AGP) each with four replications having 10 birds per replicate. All the herbal extracts and AGP were supplemented in drinking water. Ration in the form of crumble was offered to the birds ad libitum having ME=3060 kcal/kg and CP=22.5%. Body weight and feed intake were recorded weekly to calculate body weight gain (BWG) and feed conversion ratio (FCR). A total of 15 birds three from each treatment were sacrificed at the end of feeding trial and dressing parameters were evaluated. Sensory properties of broiler meat were assessed by a panel of experts. Feed intake, BWG and FCR varied (p